Correction: Characterization of an exopolysaccharide from probiont Enterobacter faecalis MSI12 and its effect on the disruption of Candida albicans biofilm. Issue 33 (4th June 2021) - Kiran, G. Seghal; Priyadharshini, S.; Anitha, K.; Gnanamani, Elumalai; Selvin, Joseph
Abstract : Correction for 'Characterization of an exopolysaccharide from probiont Enterobacter faecalis MSI12 and its effect on the disruption of Candida albicans biofilm' by G. Seghal Kiran et al., RSC Adv., 2015, 5, 71573–71585, DOI: ; 10.1039/C5RA10302A .